Teachers’ perspectives about lesson study - Richit, Adriana (2017)
This research aims to know the perspectives of elementary and middle school teachers who participated in three lesson studies about this professional development process and about their professional learning. The study follows a qualitative and interpretative approach, with data collected through interviews, which were realized in June and July of 2016, and data analysis made through content analysis. The teachers’ perspectives regarding the dynamic of lesson study development indicated that they considered this an intense process of collaboration and reflection about the elaboration of exploratory mathematical tasks and about pupils’ learning. Regarding the professional learning made possible by this process, they refer to have developed and deepened their mathematical knowledge and their knowledge of classroom strategies focused on pupils’ thinking. Besides, they indicated that the lesson studies promoted changes in terms of professional and personal relationships of the school routine.